The selective conversion of glutamic acid in amino acid mixtures using glutamate decarboxylase—a means of separating amino acids for synthesizing biobased chemicals. (19th March 2014) - Teng, Yinglai; Scott, Elinor L.; Sanders, Johan P. M.
<x xml:space="preserve">Abstract</x> Amino acids (AAs) derived from hydrolysis of protein rest streams are interesting feedstocks for the chemical industry due to their functionality. However, separation of AAs is required before they can be used for further applications. Electrodialysis may be applied to separate AAs, but its efficiency is limited when separating AAs with similar isoelectric points. To aid the separation, specific conversion of an AA to a useful product with different charge behavior to the remaining compounds is desired. Here the separation of L‐aspartic acid (Asp) and L‐glutamic acid (Glu) was studied. L‐Glutamate α‐decarboxylase (GAD, Type I, EC 4.1.1.15) was applied to specifically convert Glu into γ‐aminobutyric acid (GABA). GABA has a different charge behavior from Asp therefore allowing a potential separation by electrodialysis. Competitive inhibition and reduced operational stability caused by Asp could be eliminated by maintaining a sufficiently high concentration of Glu. Immobilization of GAD does not reduce the enzyme's initial activity. However, the operational stability was slightly reduced. An initial study on the reaction operating in a continuous mode was performed using a column reactor packed with immobilized GAD. As the reaction mixture was only passed once through the reactor, the conversion of Glu was lower than expected. To complete the conversion of Glu, the stream containing Asp and unreacted Glu might be recirculated back to the reactor after GABA has been removed. Overall, the reaction by GAD is specific to Glu and can be applied to aid the electrodialysis separation of Asp and Glu. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:681–688, 2014